An adaptive dynamical model of default contagion. Issue 7 (3rd July 2022) - Smug, Damian; Ashwin, Julian; Ashwin, Peter; Sornette, Didier
Abstract : The dynamics of default contagion is modeled in terms of adaptively coupled stochastic measures of financial health